Compound heterozygous RMND1 gene variants associated with chronic kidney disease, dilated cardiomyopathy and neurological involvement: a case report. (December 2016) - Gupta, Asheeta; Colmenero, Isabel; Ragge, Nicola; Blakely, Emma; He, Langping; McFarland, Robert; Taylor, Robert; Vogt, Julie; Milford, David
Abstract Background Nuclear gene mutations are being increasingly recognised as causes of mitochondrial disease. The nuclear geneRMND1 has recently been implicated in mitochondrial disease, but the spectrum of pathogenic variants and associated phenotype for this gene, has not been fully elucidated. Case presentation An 11-month-old boy presented with renal impairment associated with a truncal ataxia, bilateral sensorineural hearing loss, hypotonia, delayed visual maturation and global developmental delay. Over a 9-year period, he progressed to chronic kidney disease stage V and developed a dilated cardiomyopathy. Abnormalities in renal and muscle biopsy as well as cytochromec oxidase activity prompted genetic testing. After exclusion of mitochondrial DNA defects, nuclear genetic studies identified compound heterozygousRMND1 (c.713A>G, p. Asn238Ser and c.565C>T, p.Gln189*) variants. Conclusion We reportRMND1 gene variants associated with end stage renal failure, dilated cardiomyopathy, deafness and neurological involvement due to mitochondrial disease. This case expands current knowledge of mitochondrial disease secondary to mutation of theRMND1 gene by further delineating renal manifestations including histopathology. To our knowledge dilated cardiomyopathy has not been reported with renal failure in mitochondrial disease due to mutations ofRMND1 . The presence of this complication was important in this case as it precluded renal transplantation.